INFLUENCE OF SUPPLY VOLTAGE UNBALANCE ON INDUCTION MOTOR CHARACTERISTICS - GOROSHKO, ANDRII; KASHTALIAN, ANTONINA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Various power quality disturbances are present in power systems, including voltage deviation, voltage asymmetry, and voltage waveform distortion. A mathematical model of an induction motor and a model of an unbalanced three-phase supply voltage for an induction motor with a Voltage Unbalance Factor of 2% are presented. The Matlab/Simulink/Simcape software was used to simulate the squirrel-cage motor under different conditions of unbalanced voltage. A simulation model of an 11 kW three-phase induction motor was developed and the motor performance was analyzed. The dependences of the motor shaft torque, mechanical power, efficiency, and time diagrams of transient processes of direct motor starting are obtained. The voltage unbalance has a significant impact on the efficiency, power factor, and mechanical characteristics of the motor. The supply voltage asymmetry causes fluctuations in torque, mechanical power, and rotor speed. Furthermore, the frequency of torque pulsations caused by the voltage unbalance is equal to twice the fundamental frequency. Speed fluctuations cause fluctuations in centrifugal force caused by rotor imbalance. However, repeated simulations and studies of the rotor with an acceptable mass eccentricity have shown that electromagnetic torque and speed fluctuations have virtually no significant effect on the radial vibrations of the rotor and stator. But significant torque fluctuations are offset by rotor inertia, and radial unbalanced forces are small with a normal allowable eccentricity of 20 µm. It can be concluded that the asymmetry of unbalance voltages within permissible limits does not cause dangerous rotor and stator vibrations. Resonance of torsional oscillations of the rotor is possible when it is large, which is not typical for low-power induction motors.
Keywords: induction motor; Voltage unbalance; Electromagnetic Torque; Vibrations